Propylene-based copolymer compositions
By using a specific proportion of propylene and ethylene copolymer and propylene ethylene copolymer composition, combined with ultrafine talc and Ziegler-Natta catalyst, the problem of uneven optical properties and sterilization effects of extruded blow molding process products is solved, and the problem of uneven optical properties and sterilization effects is achieved. It has a balance of optical and mechanical properties after sterilization, and is suitable for the production of blow-molded items such as bottles.
Patent Information
- Application Number
- CN202380038238.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-06
- Filing Date
- 2023-05-24
- Publication Date
- 2024-12-20
AI Technical Summary
The optical properties of the extruded blow molding process products are uneven, resulting in reduced gloss and transparency, and the sterilization process has an impact on optical performance, making it difficult to find a balance between maintaining softness and improving optical performance.
72-90% propylene and ethylene copolymer and 9-28% propylene ethylene copolymer composition were used, and 0.01-100 ppm of ultrafine talc was added, and polymerized by fine-tuning the components and using Ziegler-Natta catalyst. Optimize melt flow rate and dissolution properties, combined with sterilization treatment to maintain optical and mechanical properties.
A balance between optical properties and softness of the composition after sterilization is achieved, haze is reduced, flexural modulus and chagpy impact strength is improved, and is suitable for the production of blow-molded items such as bottles.
Smart Images

Figure BDA0005116762220000061 
Figure BDA0005116762220000101 
Figure BDA0005116762220000141
Abstract
Description
Technical Field
[0001] The present invention relates to a composition comprising a propylene ethylene copolymer and ultrafine talc. The composition has particularly good optical properties in addition to mechanical properties, and in particular the composition can be sterilized to maintain good optical and mechanical properties. The composition is particularly suitable for producing blow molded articles, in particular bottles. Background Art
[0002] It is well known in the polymer field that different applications require specially tailored polymers to achieve the individual, more demanding properties. For example, a polymer used for injection molding must have other properties that are different from a polymer used for blow molding.
[0003] For example, the extrusion blow molding process is a very specific process that allows bottles of different sizes and shapes to be produced in a flexible and inexpensive manner. A major disadvantage of this process is the complex curing step compared to conventional injection molding.
[0004] Therefore, extrusion blow molded articles (such as bottles) generally exhibit inferior optical properties compared to any injection molded articles. For example, the surface properties of the interior and / or exterior of an extrusion blow molded bottle are generally non-uniform (flow lines, melt fracture), resulting in reduced overall gloss and clarity compared to an injection molded bottle or an injection stretch blow molded bottle. When it is desired to produce a soft article, the article must have low haze and low flexural modulus. High flexural modulus products are generally associated with low haze, so when it is desired to reduce the flexural modulus in order to obtain a soft product, the haze becomes worse.
[0005] Then, the medical article needs to be sterilized, and it is well known in the art that sterilization will have some deteriorating effects on the optical properties.
[0006] Therefore, it is necessary to have a polymer showing a specific balance of bending modulus and haze, so as to improve optical properties even in the presence of low modulus. In addition, it is necessary to improve the optical properties after sterilization. US 7,390,575 relates to a polyolefin-based biaxially oriented multilayer film with at least one surface layer, the surface layer comprising a propylene ethylene random block copolymer; it comprises 30 to 70% by weight of a propylene-ethylene random copolymer component (A) with an ethylene content of 1 to 7% by weight prepared in the first step of polymerization and 70 to 30% by weight of a low crystalline or amorphous propylene-ethylene random copolymer component (B) with an ethylene content of 6 to 13% by weight higher than the polymer component obtained in the first step prepared in the second step of polymerization. Preferably, the block copolymer contains an antiblocking agent. Preferred examples of antiblocking agents include organic or inorganic fine particles having an average particle size of 0.5 to 5 μm.
[0007] Applicants have discovered that a balance between optical properties and softness of the composition can be achieved by fine-tuning these two components and using talc after sterilization. Summary of the invention
[0008] Therefore, the object of the present disclosure is a polyolefin composition comprising:
[0009] A) 72 to 90 wt. % of a copolymer of propylene and ethylene, wherein:
[0010] i) an ethylene-derived unit content of 3.3 wt% to 6.0 wt%;
[0011] ii) a melting temperature ranging from 132°C to 143°C;
[0012] iii) melt flow rate (230°C / 5kg.ISO 1133) ranges from 1.1 g / 10 min to 3.5 g / 10 min;
[0013] iv) a xylene soluble matter at 25°C ranging from 4.0 wt% to 10.0 wt%;
[0014] B) 9 to 28 wt% of a propylene ethylene copolymer containing 3.6 to 7.5 wt% of ethylene-derived units and having a melt flow rate (230°C / 5kg. ISO 1133) in the range of 0.6 to 10 g / 10 min; wherein the resulting polyolefin composition has:
[0015] i) an ethylene-derived unit content of 3.5 to 5.5 wt%;
[0016] ii) the content of ethylene-derived units in the fraction soluble in xylene at 25° is from 15.2% by weight to 23.2% by weight;
[0017] iii) melt flow rate (ISO 1133 (230°C, 5kg) in the range of 1.0 g / 10 min to 4.0 g / 10 min;
[0018] iv) a xylene soluble content at 25°C ranging from 5.1 wt% to 12.0 wt%;
[0019] v) an intrinsic viscosity of the xylene soluble fraction at 25° C. in the range of 0.6 dl / g to 2.5 dl / g;
[0020] vi) the difference between the content of ethylene-derived units of component B and the content of ethylene-derived units of component A (C2B-C2A) ranges from 0.3 wt% to 4.0 wt%;
[0021] The sum of the quantities of A) and B) is 100
[0022] C) from 10000 ppm (1.0 wt. %) to 100 ppm (0.01 wt. %) of talc having a particle size distribution comprised between 0.5 μm and 5 μm and a specific surface area BET (ISO 9277:2010) higher than 15 m 2 / g;
[0023] ppm is calculated as the sum of the amounts of A+B. DETAILED DESCRIPTION
[0024] Therefore, the object of the present disclosure is a polyolefin composition comprising:
[0025] A) 72 to 90 wt.-%, preferably 73 to 88 wt.-%, more preferably 74 to 86 wt.-% of a copolymer of propylene and ethylene, wherein:
[0026] i) the content of ethylene-derived units is from 3.3 wt% to 6.0 wt%; preferably from 3.5 wt% to 5.5 wt%; more preferably from 3.7 wt% to 4.8 wt%;
[0027] (ii) a melting temperature ranging from 132°C to 143°C; preferably ranging from 134°C to 142°C; more preferably ranging from 136°C to 141°C;
[0028] (iii) melt flow rate (230°C / 5kg.ISO 1133) ranging from 1.1 g / 10 min to 3.5 g / 10 min; preferably ranging from 1.2 g / 10 min to 2.5 g / 10 min; more preferably ranging from 1.3 g / 10 min to 2.0 g / 10 min;
[0029] (iv) xylene solubles at 25°C range from 4.0 wt% to 10.0 wt%; preferably range from 4.5 wt% to 9.0 wt%; more preferably range from 5.2 wt% to 8.0 wt%;
[0030] B) 9 to 28 wt%, preferably 13 to 27 wt%, more preferably 14 to 26 wt% of a propylene ethylene copolymer containing 3.6 to 7.5 wt%, preferably 3.8 to 7.0 wt%, more preferably 4.0 to 6.8 wt% of ethylene derived units; wherein the resulting polyolefin composition has:
[0031] i) the content of ethylene-derived units is from 3.5 wt% to 5.5 wt%; preferably from 3.8 wt% to 5.3 wt%; more preferably from 3.9 wt% to 5.0 wt%;
[0032] ii) the content of ethylene-derived units in the xylene-soluble fraction at 25° is from 15.2% to 23.2% by weight; preferably from 16.3% to 22.2% by weight; more preferably from 17.2% to 21.3% by weight;
[0033] iii) melt flow rate (ISO 1133 (230°C, 5kg) ranging from 1.0 g / 10 min to 4.0 g / 10 min; preferably ranging from 1.1 g / 10 min to 2.9 g / 10 min; more preferably ranging from 1.2 g / 10 min to 2.5 g / 10 min;
[0034] iv) xylene solubles at 25°C ranging from 5.1 wt% to 12.0 wt%; preferably ranging from 5.5 wt% to 11.0 wt%; more preferably ranging from 6.0 wt% to 10.0 wt%;
[0035] v) the intrinsic viscosity of the xylene soluble fraction at 25° C. ranges from 0.6 dl / g to 2.5 dl / g; preferably ranges from 0.8 dl / g to 2.0 dl / g; more preferably ranges from 1.0 dl / g to 1.8 dl / g;
[0036] vi) the difference between the content of ethylene derived units of component B and the content of ethylene derived units of component B (C2B-C2A) ranges from 0.3 to 4.0 wt. %; preferably ranges from 0.4 to 3.5 wt. %; more preferably ranges from 0.4 to 3.0 wt. %;
[0037] The sum of the quantities of a), b) and c) is 100;
[0038] C) from 10000 ppm (1.0 wt%) to 100 ppm (0.01 wt%); preferably from 8000 ppm (0.8 wt%) to 300 ppm (0.03 wt%); more preferably from 4000 ppm (0.4 wt%) to 500 ppm (0.05 wt%) of talc; having a particle size distribution of 0.5 to 5 μm measured with a SediGraph 5100 particle size analysis system and a specific surface area BET (ISO9277:2010) higher than 15 m 2 / g; preferably at 15m 2 / g to 25m 2 / g range; preferably 16m 2 / g to 23m 2 / g; more preferably 17m 2 / g to 21m 2 / g;
[0039] ppm is calculated as the sum of the amounts of A+B.
[0040] The term copolymer necessarily refers to binary copolymers containing two monomers (propylene and ethylene).
[0041] The polyolefin composition disclosed herein is particularly suitable for the production of blow molded articles, in particular bottles. Furthermore, the composition is particularly suitable for sterilization to obtain medical articles. The sterilization process comprises a step of heating the polymer at 121°C for 30 minutes.
[0042] The polyolefin composition preferably has one or more of the following characteristics:
[0043] i) the difference between the haze measured before and after sterilization (Δhaze) is in the range of 0.1 to 8.0, the haze being measured on a 1 mm plate according to the method described in the Examples;
[0044] ii) a flexural modulus (ASTM D 790) ranging from 600 MPa to 950 MPa; preferably from 670 MPa to 920 MPa; even more preferably from 700 MPa to 900 MPa;
[0045] iii) 20.0 kj / m at 23°C 2 Up to 45.0 kj / m 2 Charpy impact strength within the range; preferably 23.0 kj / m 2 Up to 40.0 kj / m 2 ; The more preferred range is 25.0 kj / m 2 Up to 35.0 kj / m 2 ;
[0046] iv) The specific surface area of the ultrafine talc component C) is in the range of 15 m 2 / g to 20m 2 / g, preferably 17m 2 / g to 19m 2 / g.
[0047] The polyolefin composition of the invention is particularly suitable for obtaining small blow-molded articles, such as bottles. In fact, by adding component C), the haze after sterilization is lower than that of a composition containing no content of component C).
[0048] Another object of the present invention is therefore a bottle comprising the composition according to the invention.
[0049] Small blow molded articles can be manufactured by various industrial processes known in the art.
[0050] The composition of the present invention can be prepared by blending components A) and B).
[0051] The polymerization of A) and B) can be carried out in the presence of a Ziegler-Natta catalyst. An essential component of the catalyst is a solid catalyst component comprising a titanium compound having at least one titanium-halogen bond and an electron donor compound, both of which are supported in active form on a magnesium halide. Another essential component (cocatalyst) is an organoaluminum compound, such as an alkylaluminum compound.
[0052] An external donor may be added optionally.
[0053] The catalysts typically used in the process of the present invention are capable of producing polypropylene having a xylene insolubility value at ambient temperature greater than 90%, preferably greater than 95%.
[0054] Catalysts having the above characteristics are well known in the patent literature; particularly advantageous are the catalysts described in US Pat. No. 4,399,054 and European Patent No. 45977. Other examples can be found in US Pat. No. 4,472,524.
[0055] The solid catalyst component used in the catalyst comprises as an electron donor (internal donor) a compound selected from the group consisting of ethers, ketones, lactones, compounds containing N, P and / or S atoms, and esters of mono- and dicarboxylic acids.
[0056] Particularly suitable electron donor compounds are esters of phthalic acid and 1,3-diethers of the following formula:
[0057]
[0058] Where R I and R II Same or different and C1-C 18 Alkyl, C3-C 18 Cycloalkyl or C7-C 18 Aryl radical; R III and R IVare identical or different and are C1-C4 alkyl radicals; or are 1,3-diethers, wherein the carbon atom in position 2 belongs to a cyclic or polycyclic structure consisting of 5, 6 or 7 carbon atoms or 5-n or 6-n' carbon atoms and n nitrogen atoms and n' heteroatoms selected from the group consisting of N, O, S and Si, respectively, wherein n is 1 or 2 and n' is 1, 2 or 3, said structure containing two or three degrees of unsaturation (cyclopolyene structure) and optionally condensed with other cyclic structures or substituted with one or more substituents selected from the group consisting of linear or branched alkyl radicals, cycloalkyl, aryl, aralkyl, alkaryl radicals and halogen, or condensed with other cyclic structures and substituted with one or more of the above substituents, one or more of which may also be bonded to the condensed cyclic structure; one or more of the above alkyl, cycloalkyl, aryl, aralkyl or alkaryl radicals and a condensed cyclic structure optionally containing one or more heteroatoms as substituents for carbon atoms or hydrogen atoms or both.
[0059] Ethers of this type are described in published European Patent Applications 361,493 and 728,769.
[0060] Representative examples of the diethers are 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 9,9-bis(methoxymethyl)fluorene.
[0061] Other suitable electron donor compounds are phthalic acid esters, such as diisobutyl phthalate, dioctyl phthalate, diphenyl phthalate and benzyl butyl phthalate.
[0062] The preparation of the above-mentioned catalyst components is performed according to various methods.
[0063] For example, MgCl2.nROH adduct (especially in the form of spherical particles) (where n is generally from 1 to 3 and ROH is ethanol, butanol or isobutanol) is reacted with an excess of TiCl4 containing an electron donor compound. The reaction temperature is generally 80° C. to 120° C. The solid is then separated and reacted once more with TiCl4 in the presence or absence of an electron donor compound, after which it is separated and washed with an aliquot of a hydrocarbon until all chloride ions are gone.
[0064] In the solid catalyst component, the titanium compound, denoted Ti, is generally present in an amount of 0.5 to 10% by weight. The amount of electron donor compound remaining fixed on the solid catalyst component is generally 5 to 20 mol% relative to the magnesium dihalide.
[0065] Titanium compounds which can be used for the preparation of the solid catalyst component are titanium halides and halogen alcoholates. Titanium tetrachloride is the preferred compound.
[0066] The above reactions form magnesium halides in active form. Other reactions are known in the literature which, starting from magnesium compounds other than halides, such as magnesium carboxylates, form magnesium halides in active form.
[0067] Al-alkyl compounds used as co-catalysts include Al-trialkyls such as Al-triethyl, Al-triisobutyl, Al-tri-n-butyl and linear or cyclic Al-alkyl compounds containing two or more Al atoms bonded to each other via O or N atoms or SO4 or SO3 groups.
[0068] The Al-alkyl compound is generally used in such an amount that the Al / Ti ratio is 1 to 1000.
[0069] Electron donor compounds that can be used as external donors include aromatic acid esters, such as alkyl benzoates, and in particular silicon compounds containing at least one Si-OR bond, wherein R is a hydrocarbon radical.
[0070] Examples of silicon compounds are (tert-butyl)2Si(OCH3)2, (cyclohexyl)(methyl)Si(OCH3)2, (cyclopentyl)2Si(OCH3)2 and (phenyl)2Si(OCH3)2 and (1,1,2-trimethylpropyl)Si(OCH3)3.
[0071] 1,3-Diethers of the abovementioned formula can also be used advantageously. If the internal donor is one of these diethers, the external donor can be omitted.
[0072] In particular, component A) is preferably prepared by using a catalyst containing a phthalate as internal donor and (cyclopentyl)2Si(OCH3)2 as external donor, or the 1,3-diether as internal donor, even though many other combinations of the aforementioned catalyst components may allow obtaining the composition according to the invention.
[0073] The Ziegler-Natta catalyst that can be used to prepare the propylene polymer of the present invention is a solid catalyst component comprising a magnesium halide, a titanium compound having at least one titanium-halogen bond as described above and at least two electron donor compounds, one of which is selected from succinates and the other is selected from 1,3-diethers.
[0074] Component B) can be prepared by using the above-mentioned catalyst system or by using a metallocene-based catalyst system. Component B) can be obtained by using a gas phase polymerization process, a slurry polymerization process or a solution polymerization process.
[0075] It is also possible to prepare components (A) and (B) in a continuous sequential polymerization process, wherein component A) is prepared in a first reactor and component (B) is prepared in a second reactor in the presence of component A) according to known techniques and operating in the gas phase or in the liquid phase with or without an inert diluent, or by a mixed liquid-gas technique.
[0076] The following examples are given for illustration of the present invention and not for limiting purposes.
[0077] Examples
[0078] Characterization methods
[0079] Melting temperature and crystallization temperature: determined by differential scanning calorimetry (DSC)
[0080] Weigh 6±1 mg of sample, heat to 220±1°C at a rate of 20°C / min in a nitrogen stream and keep at 220±1°C for 2 minutes, then cool to 40±2°C at a rate of 20°C / min, and keep at this temperature for 2 minutes to crystallize the sample. Then, heat to 220°C±1 at a rate of 20°C / min to melt the sample again. Record the melting scan, obtain the thermogram, and read the melting temperature and crystallization temperature from it.
[0081] Melt flow rate: measured according to method ISO 1133 (230°C, 5 kg).
[0082] Xylene soluble fraction at 25°C (XS)
[0083] The xylene solubles at 25°C have been determined according to ISO 16152:2005; the solution volume is 250 ml, precipitation is carried out at 25°C for 20 minutes, with 10 minutes of stirring (magnetic stirrer) of the solution, and drying at 70°C.
[0084] Intrinsic viscosity (IV)
[0085] The sample was dissolved in tetralin at 135°C and then poured into a capillary viscometer.
[0086] The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass jacket; this setup allows temperature control with a circulating thermostatic liquid.
[0087] The downward passage of the meniscus is timed by a photoelectric device. The meniscus' passage in front of the upper lamp starts a counter with a quartz crystal oscillator. When it passes the lower lamp, the meniscus stops the counter and the outflow time is recorded: This is converted to an intrinsic viscosity value by the following method
[0088] Haze (on 1mm plate)
[0089] According to the method used, 5×5 cm specimens are cut into 1 mm thick molded plaques and the haze value is measured using a Gardner photometric device connected to a UX-10 Hazemeter or an equivalent instrument with a GE1209 light source and filter "C". Reference samples of known haze are used to calibrate the instrument. The plaques to be tested are produced according to the following method.
[0090] Plaques of 75 x 75 x 1 mm were molded using a 90 ton GBF Plastiniector G235190 injection molding machine under the following processing conditions:
[0091] Screw speed: 120rpm
[0092] Back pressure: 10 bar
[0093] Melting temperature: 260℃
[0094] Injection time: 5 seconds
[0095] Switch to holding pressure: 50 bar
[0096] First stage holding pressure: 30 bar
[0097] Second stage pressure: 20 bar
[0098] Maintain pressure curve: 5 seconds in the first stage
[0099] Second stage 10 seconds
[0100] Cooldown: 20 seconds
[0101] Mold water temperature: 40℃
[0102] Ethylene content in copolymer
[0103] The data were collected on a Bruker AV-600 spectrometer equipped with a cryoprobe. 13 C NMR spectroscopy, operated at 160.91 MHz at 120 °C in Fourier transform mode.
[0104] Sββ carbon (according to "through 13C NMR measures monomer sequence distribution in ethylene-propylene rubber. 3. Use of Reaction Probability Mode" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, vol. 10, p. 536) peak was used as an internal reference with a value of 29.9 ppm. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 120°C at a concentration of 8% wt / v. Each spectrum was acquired with a 90° pulse with a 15 s delay between the pulse and the CPD to eliminate 1 H- 13 C coupling. 512 transient data were stored in 32K data points using a spectral window of 9000 Hz.
[0105] According to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titaniumtrichloride-diethyl-aluminum chloride", M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 1982, No. 15, p. 1150), the spectra were assigned using the following equations, and the triad distribution and composition were evaluated:
[0106] PPP=100Tββ / S PPE=100Tβδ / S EPE=100Tδδ / S
[0107] PEP=100Sββ / S PEE=100Sβδ / S EEE=100(0.25Sγδ+0.5Sδδ) / S
[0108] S=Tββ+Tβδ+Tδδ+Sββ+Sβδ+0.25Sγδ+0.5Sδδ
[0109] The mole percentage of ethylene content was estimated using the following equation:
[0110] E%mol=100*[PEP+PEE+EEE]. The weight percent of ethylene content was estimated using the following equation:
[0111] 100*E%mol*MWE
[0112] E%wt.=E%mol*MWE+P%mol*MWP
[0113] Where P%mol is the molar percentage of propylene content, and MWE and MWP are the molecular weights of ethylene and propylene, respectively.
[0114] The product of the reactivity ratios r1r2 is calculated according to Carman (CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977; No. 10, p. 536) as follows:
[0115]
[0116] According to PPP mmT ββ (28.90 to 29.65ppm) and total T ββ The stereoregularity of the propylene sequence was calculated as the mm content by the ratio of (29.80 to 28.37 ppm).
[0117] Impact test: ISO 180
[0118] Preparation of injection molded samples: Test specimens of 80×10×4 mm were obtained according to method ISO 1873-2:2007.
[0119] Flexural modulus
[0120] Measured according to ASTM D 790 on injection molded specimens.
[0121] Charpy impact test at 23°C: measured on injection molded specimens according to ISO 179-1:2010.
[0122] Specific surface area BET
[0123] Measured according to ISO 9277:2010.
[0124] Particle size distribution
[0125] The measurements were performed using a SediGraph 5100 particle size analysis system.
[0126] Example 1 according to the present invention
[0127] Catalyst system
[0128] The Ziegler-Natta catalyst was prepared according to Example 5, lines 48 to 55 of European Patent EP728769. Triethylaluminum (TEAL) was used as a cocatalyst and dicyclopentyldimethoxysilane (DCPMS) as an external donor in the weight ratios shown in Table 1.
[0129] Prepolymerization
[0130] Before the solid catalyst component is introduced into the polymerization reactor, it is suspended in liquid propylene at 20°C for about 5 minutes and then introduced into the first polymerization reactor for prepolymerization.
[0131] polymerization
[0132] The polymerization experiments were carried out in a series of three reactors in a continuous mode, which were equipped with a device to transfer the product from one reactor to another reactor next to it. The first two reactors were liquid phase reactors, and the third was a fluidized bed gas phase reactor. Component (A) was prepared in the first and second reactors, while component (B) was prepared in the third reactor.
[0133] Hydrogen was used as a molecular weight regulator.
[0134] The gas phase (propylene, ethylene and hydrogen) was analyzed continuously by gas chromatography.
[0135] At the end of the experiment, the powder was discharged and dried under a stream of nitrogen. The main polymerization conditions are reported in Table 1.
[0136] Table 1
[0137] Example 1 Example 2 TEAL / solid catalyst component weight ratio 9.2 9.3 TEAL / DCPMS weight ratio 3 4 Liquid Phase Reactor Polymerization temperature ℃ 67 67 pressure Gauge pressure 39 39 Dwell time minute 51 53 H2 feed molppm 401 420 C2 / (C2+C3) Molar Ratio 0.049 0.050 Polymerization temperature ℃ 80 80 pressure Gauge pressure 18 18 Dwell time minute 49 52 C2 / (C2+C3) Molar Ratio 0.052 0.062 H2 / C2 Molar Ratio 0.083 0.082
[0138] C2 = ethylene; C3 = propylene; H2 = hydrogen
[0139] Table 2 reports the characteristics of the compositions of Examples 1 to 3 and Comparative Example 4
[0140] Examples Example 1 Example 3 Component A) Ethylene content weight% 4.0 4.3 MFR g / 10' 1.5 1.6 Xylene soluble matter at 25℃ weight% 6.0 6.4 Melting temperature ℃ 139 137.5 Component B) Splinter weight% 25 22 Ethylene content in component b) weight% 5.2 6.1 Characteristics of the composition Xylene soluble matter at 25℃ weight% 7.2 9.0 MFR g / 10' 1.31 2.23 XSIV (XS intrinsic viscosity) dl / g 1.36 1.25 Ethylene content in the xylene soluble fraction weight% 20.2 17.9 Ethylene content weight% 4.3 4.7
[0141] Components A and B have been blended with talc (component C) having a particle size distribution of 0.5 to 5 μm and 18 μm 2 As a comparative example, a particle size distribution of 0.5 to 5 μm and 13 m 2 / g surface area (BETT) of commercial talc HM05.
[0142] The characterization results of the compositions are reported in Table 3.
[0143] Table 3
[0144]
[0145] Table 3 (continued)
[0146]
[0147] According to the results of Table 3, the haze result of the composition according to the present invention after sterilization is lower, which is not the case before sterilization. Therefore, the sterilized composition according to the present disclosure has lower haze.
Claims
1. A polyolefin composition comprising: A) 72 to 90 wt. % of a copolymer of propylene and ethylene, wherein: i) a content of ethylene-derived units of 3.3 to 6.0 wt% as measured by NMR; (ii) a melting temperature ranging from 132° C. to 143° C. as measured by DSC; (iii) melt flow rate (230°C / 2.16 kg. ISO 1133) ranging from 1.1 g / 10 min to 3.5 g / 10 min; (iv) a xylene soluble content at 25° C. ranging from 4.0 wt % to 10.0 wt %; B) 9 to 28 wt% of a propylene ethylene copolymer containing 3.6 to 7.5 wt% of ethylene-derived units measured by NMR, with a melt flow rate (230°C / 2.16 kg. ISO 1133) in the range of from 0.6 to 10 g / 10 min; The obtained polyolefin composition has: i) a content of ethylene-derived units of 3.5 to 5.5 wt% as measured by NMR; ii) a content of ethylene-derived units in the fraction soluble in xylene at 25°, measured by NMR, of from 15.2% to 23.2% by weight; iii) melt flow rate (ISO 1133 (230°C, 2.16 kg) in the range of 1.0 g / 10 min to 4.0 g / 10 min; iv) a xylene soluble content at 25°C ranging from 5.1 wt% to 12.0 wt%; v) the intrinsic viscosity of said fraction of xylene solubles at 25°C, measured in tetralin at 135°C, ranges from 0.6 dl / g to 2.5 dl / g; vi) the difference between the ethylene-derived unit content of component B and the ethylene-derived unit content of component A (C2B-C2A) ranges from 0.3 wt% to 5.0 wt%; The sum of the quantities of A) and B) is 100; From 10000 ppm to 100 ppm of talc having a particle size distribution comprised between 0.5 μm and 5 μm and a particle size distribution greater than 15 μm as measured with a SediGraph 5100 particle size analysis system. 2 / g specific surface area BET (ISO 9277:2010); ppm is calculated as the sum of the amounts of A+B.
2. The polyolefin composition according to claim 1, wherein the content of ethylene-derived units in component A) ranges from 3.5 wt.-% to 5.5 wt.-%.
3. The polyolefin composition according to any one of claims 1 to 2, wherein in component A), the melt flow rate (230°C / 2.16 kg. ISO 1133) ranges from 1.2 g / 10 min to 2.5 g / 10 min.
4. The polyolefin composition according to any one of claims 1 to 4, wherein in component A), the xylene solubles at 25°C range from 4.5 wt% to 9.0 wt%.
5. The polyolefin composition according to any one of claims 1 to 5, wherein in component B), the ethylene-derived units content ranges from 3.8 wt% to 7.0 wt%.
6. The polyolefin composition according to any one of claims 1 to 5, wherein the content of ethylene derived units measured by NMR is from 3.8 to 5.3 wt%.
7. The polyolefin composition according to any one of claims 1 to 6, wherein the content of ethylene-derived units in the fraction soluble in xylene at 25° measured by NMR is between 16.3% and 22.2% by weight.
8. The polyolefin composition according to any one of claims 1 to 7, wherein the melt flow rate (ISO 1133 (230°C, 2.16 kg)) ranges from 1.1 g / 10 min to 2.9 g / 10 min.
9. The polyolefin composition according to any one of claims 1 to 8, wherein the xylene solubles at 25°C range from 5.5 wt% to 11.0 wt%.
10. The polyolefin composition according to any one of claims 1 to 9, wherein the intrinsic viscosity of the fraction soluble in xylene at 25°C measured in tetralin at 135°C ranges from 0.8 dl / g to 2.0 dl / g.
11. The polyolefin composition according to any one of claims 1 to 10, wherein in component C), the specific surface area is in the range of 15 m2 / s by BET (ISO 9277:2010). 2 / g to 25m 2 / g.
12. The polyolefin composition according to any one of claims 1 to 11, wherein component A) ranges from 73 wt% to 88 wt% and component B) ranges from 13 wt% to 27 wt%, calculated as the sum of A9+B).
13. The polyolefin composition according to any one of claims 1 to 12, wherein the content of ethylene-derived units in the fraction soluble in xylene at 25° measured by NMR is between 17.2% and 21.3% by weight.
14. A small blow-molded article comprising the polyolefin composition according to any one of claims 1 to 12.
15. A bottle comprising the polyolefin composition according to any one of claims 1 to 12.
